PERFORMANCE, HETEROSIS AND HERITABILITY IN SINGLE, THREE-WAY AND DOUBLE CROSS HYBRIDS OF MAIZE ( Y AND DOUBLE CROSS HYBRIDS OF MAIZE (Zea mays Zea mays L.). - K. SUMALINI; T. PRADEEP; D. SRAVANI (The Bioscan, 2019)
Performance, heterosis and heritability were studied in a set of single, three-way and double crosses involving seven inbreds for thirteen yield and yield contributing characters across three locations. Three-way crosses and double crosses were found to be more variable than single crosses for days to maturity, ear diameter, number of kernels row -1 and grain yield and are more advantageous when crop is grown under adverse climatic conditions and had shown stable and consistent performance. Heterosis estimates were low for majority of the traits studied in all the three classes of hybrids. Narrow sense heritability was moderate for 50 per cent tasseling, days to 50 per cent silking, number of kernel rows ear -1 , and shelling percentage and low for ear length, ear diameter, number of kernels row -1 ,grain and fodder yield at all the individual locations indicating predominance of dominant gene action. From all the three classes of crosses, one each of superior single [SC-2; BML-51 × BML-14], three-way [TWC-51; (BML-32 × BML-6) × BML-51] and double [DC-18; (BML-51 × BML-14) × (BML-10 × BML-7)] cross hybrids were identified based on high per se performance at least in two locations.